PENGGUNAAN DANA RUANG TERBUKA HIJAU LAIN PERUNTUKAN (STUDI KASUS: PUTUSAN NOMOR 22/PID.SUS-TPK/2018/PN.PLK) - Paulus Marulam Marbun (The Juris, 2019)
Procurement of goods and services or in foreign terms called procurement arises because of the need for goods for services such as stationery, medical equipment, fuel belonging to government vehicles, maintenance of government buildings where the implementation must be in accordance with the provisions of the legislation applies, because in the implementation of the procurement of government goods and services concerning Ministries / Institutions / Work Units of the Regional Apparatus / Government Institutions in a large enough amount or value, the procedures and procedures are clearly regulated and detailed in the applicable laws and regulations . The problem is how are the legal arrangements for the use of green open living funds? How is the legal practice of using green open space funds outside of their designation? And how about the deviation of funds from the use of green open space funds in the case of a court decision? This research is included in the form of normative juridical research. The conclusion is that in legal practice the use of green open space funds outside of its designation, namely in the legal practice, the procurement of goods and services starts from the purchase / sale of goods on the market directly (in cash), then develops towards the purchase of a payment term, by making documents accountability (buyer and seller), and ultimately through procurement through an auction process. In the process, the procurement of goods and services involves several related parties, so there needs to be ethics, norms, and principles for the procurement of goods and services to be able to regulate or be used as the basis for determining the policies for the procurement of goods and services.